Enantioselective Total Synthesis and Structure Confirmation of the Natural Dimeric Tetrahydroxanthenone Dicerandrol C. Issue 10 (25th January 2017) - Ganapathy, Dhandapani; Reiner, Johannes R.; Valdomir, Guillermo; Senthilkumar, Soundararasu; Tietze, Lutz F.
Abstract: The first enantioselective total synthesis of natural dicerandrol C (1 c ) as its enantiomer containing a dimeric tetrahydroxanthenone skeleton is described starting from the enantiopure chromane6 which was obtained through a Wacker‐type cyclization with >99 % ee . For the formation of the dimeric skeleton a palladium‐catalyzed Suzuki reaction was used. The synthesis allowed the confirmation of the absolute configuration of the dicerandrols. Abstract : All natural : The first enantioselective total synthesis of a natural dicerandrol containing a dimeric tetrahydroxanthenone skeleton is described starting from an enantiopure chromane, which was obtained through a Wacker‐type cyclization with >99 % ee . For the formation of the dimeric skeleton a palladium‐catalyzed Suzuki reaction was used. The synthesis allowed an unambiguous proof of the absolute and relative configuration of the natural product.